Biomimetic on-chip assay reveals the anti-metastatic potential of a novel thienopyrimidine compound in triple-negative breast cancer cell lines - Sigdel, Indira; Ofori-Kwafo, Awurama; Heizelman, Robert J.; Nestor-Kalinoski, Andrea; Prabhakarpandian, Balabhaskar; Tiwari, Amit K.; Tang, Yuan (Frontiers in Bioengineering and Biotechnology, 2023)
This study presents a microfluidic tumor microenvironment (TME) model for evaluating the anti-metastatic efficacy of a novel thienopyrimidines analog with anti-cancer properties utilizing an existing commercial platform. The microfluidic device consists of a tissue compartment flanked by vascular channels, allowing for the co-culture of multiple cell types and providing a wide range of culturing conditions in one device. Human metastatic, drug-resistant triple-negative breast cancer (TNBC) cells (SUM159PTX) and primary human umbilical vein endothelial cells (HUVEC) were used to model the TME. A dynamic perfusion scheme was employed to facilitate EC physiological function and lumen formation. The measured permeability of the EC barrier was comparable to observed microvessels permeability in vivo. The TNBC cells formed a 3D tumor, and co-culture with HUVEC negatively impacted EC barrier integrity. The microfluidic TME was then used to model the intravenous route of drug delivery. Paclitaxel (PTX) and a novel non-apoptotic agent TPH104c were introduced via the vascular channels and successfully reached the TNBC tumor, resulting in both time and concentration-dependent tumor growth inhibition. PTX treatment significantly reduced EC barrier integrity, highlighting the adverse effects of PTX on vascular ECs. TPH104c preserved EC barrier integrity and prevented TNBC intravasation. In conclusion, this study demonstrates the potential of microfluidics for studying complex biological processes in a controlled environment and evaluating the efficacy and toxicity of chemotherapeutic agents in more physiologically relevant conditions. This model can be a valuable tool for screening potential anticancer drugs and developing personalized cancer treatment strategies.